RURAL DEVELOPMENT NETWORK AND TERRITORIAL COMPETITIVENESS - Popović, Vesna; Katić, Branko; Živanović- Miljković, Jelena (Economics of Agriculture, 2018)
In this paper, as a case-study, the authors examine development potentials and capacity building of local actors in one of the future NUTS III regions of Serbia, functional region Kolubara–Mačva-Podrinje, that encompass 14 municipalities of Kolubara and Mačva districts. The results of the situation analysis, including SWOT matrix, indicate local actors animation and its regional networking as one of the basic factors of territorial development.